Ergonomic Improvements In The Printed Circuit Assembly Factories Of The Multimedia Industries In Malaysia - Yeow, Paul Heng Ping (2002)
The research objective is to create and use a new ergonomic method called the Ergonomic Weighted Score (EWS) and to use existing ergonomic methods for improvements in areas such as quality, productivity, Occupational Health and Safety (OHS) and cost-effectiveness in some Printed Circuit Assembly (PCA) factories in Malaysia, an Industrially Developing Country (IDC).